Pseudomonas fluorescens and Azospirillum brasilense Increase Yield and Fruit Quality of Tomato Under Field Conditions - Pérez Rodriguez, María Micaela; Pontin, Mariela Ana; Lipinski, Victor Mario; Bottini, Ambrosio Rubén; Piccoli, Patricia Noemí; Cohen, Ana Carmen (Springer, 2020)
Crop inoculation with plant growth-promoting rhizobacteria (PGPR) is a sustainable alternative to diminish the excessive use of chemical fertilizers in agriculture. However, there is little information about PGPR inoculation effects under field conditions and even less on industrial tomato production. We aimed to study the effects of a sole inoculation at seedling stage with Pseudomonas fluorescens Rt6M10, Azospirillum brasilense Az39, and their combination on growth and yield of two industrial tomato varieties UCO 14 (UCO) and Harris Moran 3861 (HM). We compared these PGPR inoculation treatments with chemically fertilized and non-fertilized (control) seedlings under field conditions. We found that inoculation with Rt6M10, Az39, and their combination increased seedling root dry weight by 62%, 41%, and 23%, respectively and shoot dry weight by 29%, 23%, and 2%, respectively compared with non-inoculated control, improving tolerance to transplant stress. Inoculation with Rt6M10, Az39, and their combination increased stem diameter by 15%, 16%, and 13%, respectively, while Rt6M10 and the combination treatments increased leaf chlorophyll and carotenoid levels compared with non-inoculated plants. Az39 increased fruit number (35%) and fruit weight (38%) per plant in HM, whereas in UCO variety, the increase was the highest (48% and 49%, respectively). Seedling inoculation increase fruit firmness and equatorial and polar fruit diameter by 24%, 10%, and 12%, respectively in HM and by 21%, 14%, and 14%, respectively in UCO. Overall, bio-inoculation with Rt6M10 and/or Az39 was beneficial for tomato seedlings at transplanting and supported fruit yield and quality (total soluble solid content, pH, and titratable acidity) equally or better than chemically fertilized seedlings.